Dentoskeletal Parameters Comparison of Different Types of Overbite in Class I Occlusion (Lateral Cephalomtric Study) - Fadhil Y Jassim; Khawla M Awni (University of Mosul, College of Dentistry, 2014)
This study is intended to evaluate the skeletofacial and dental parameters in different types of overbite and to compare among them. Materials and Methods: It was carried out on a sample of 150 Iraqi adolescents (65 males and 85 females), aged (12-15) years with class I malocclusion have different overbite (open, normal and deep bites).The sample were selected according to certain criteria among the students of intermediate schools in the center of Mosul city. Lateral cephalometric radiograph was taken for each subject. Twenty-one cephalometric measurements (nine angular and twelve linear) and five ratios had been determined. Results: There are significant differences among the three types of overbite concerning total anterior facial height, upper anterior facial height and lower anterior facial height variables. Also, upper posterior dental height and lower posterior dental height show a significant difference between them. Anterior cranial base to mandibular plane angle, palato mandibular plane angle, occluso-mandibular plane angle, gonial angle and summation of posterior angles are significantly different among the different types of overbite in both sexes and the total sample. All skeletal and dental ratios are significantly different among the three types of overbite in both sexes and total sample. Conclusions: The study concludes that open bite group possesses significant higher values of total and lower anterior facial height, upper and lower posterior dental height, while deep bite group possesses significant higher value of upper anterior facial height.